Postmenopausal osteoporosis: pathophysiology, diagnosis, compliance with drug therapy. Original and generic drugs - V. P. Smetnik (Медицинский совет, 2013)
Osteoporosis (OP) is a chronic progressive disease of the skeleton decreasing bone strength and leading to fractures as a result of minor injuries. Postmenopausal osteoporosis (PMO) primarily occurs in peri-and postmenopausal women. Availability of efficient and affordable generic drugs in the market helps a greater number of patients to undergo treatment.